Branchinotogluma bipapillata n. sp., a new branchiate scale worm (Annelida: Polynoidae) from two hydrothermal fields on the Southwest Indian Ridge - Zhou, Yadong; Wang, Yueyun; Zhang, Dongsheng; Wang, Chunsheng (Zootaxa, 2018)
A new species of Branchinotogluma, found at two hydrothermal vent fields on Southwest Indian Ocean Ridge, is described herein. It can be distinguished from its congeners by the small acicular lobe on the tentacular segment, the stout smooth notochaetae, 5 pairs of dorsal and ventral papillae surrounding the pharynx, 2 pairs of long ventral papillae and 4 pairs of ventral lamellae on males, and modified parapodia on posterior segments. Sexual dimorphism is also reported in the new species, as male and female individuals display differences in characters on the ventral papillae and posterior segments.